[Antal Kiss 1]
1970-1977, Kiskunfélegyháza Petőfi statue, family, child, vintage, weekend-house, Christmas glove-puppets, family, children drawing, old lady's birthday, wedding, Zakopane, mountains, newborn baby, agricultural co-operative, Finland, Balaton, 1972 the sea in Bulgaria